2021
DOI: 10.3354/meps13638
|View full text |Cite
|
Sign up to set email alerts
|

Age-specific behavior and habitat use in humpback whales: implications for vessel strike

Abstract: Vessel strikes are a major threat impacting large whales globally. Juvenile whales often represent a high proportion of lethal vessel strikes, but few studies have investigated whether juvenile whales show different behaviors that might influence their risk of vessel strike. We evaluated how variability in habitat use and foraging behavior by age class influences the risk of vessel strike for humpback whales Megaptera novaeangliae in the New York Bight (NYB), a highly urbanized region with frequent vessel stri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
24
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(25 citation statements)
references
References 62 publications
1
24
0
Order By: Relevance
“…Thus, it is conceivable that the young age of individuals in the NYBA may have biased matches toward the GoM considering the extensive effort employed there to catalogue whales from the year of birth. The young age structure in the nearshore waters of the NYBA is consistent with recent work by Stepanuk et al (2021) in the greater New York Bight, and as described by Swingle et al (1993), Barco et al (2002) and Aschettino et al (2020) for live whales from the USMA. It is also consistent with the primary age-class of stranded humpback whales found in the USMA from 1985-2000 (Wiley et al, 1995;Barco et al, 2002) and whales catalogued in the NYBA that were found stranded.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Thus, it is conceivable that the young age of individuals in the NYBA may have biased matches toward the GoM considering the extensive effort employed there to catalogue whales from the year of birth. The young age structure in the nearshore waters of the NYBA is consistent with recent work by Stepanuk et al (2021) in the greater New York Bight, and as described by Swingle et al (1993), Barco et al (2002) and Aschettino et al (2020) for live whales from the USMA. It is also consistent with the primary age-class of stranded humpback whales found in the USMA from 1985-2000 (Wiley et al, 1995;Barco et al, 2002) and whales catalogued in the NYBA that were found stranded.…”
Section: Discussionsupporting
confidence: 90%
“…Extended occupancy in the NYBA has the potential to increase individual overlap with human activities. Increasing sightings in and around shipping lanes in the New York Bight and greater USMA (Brown et al, 2019;Aschettino et al, 2020;King et al, 2021;Stepanuk et al, 2021;Zoidis et al, 2021;Smith et al, 2022) may be a significant factor in the latest Unusual Mortality Event for humpback whales along the Atlantic Coast. The recent designation of several Wind Energy Areas within the New York Bight (BOEM, 2021) will inevitably lead to an increase in vessel traffic (Dolman & Simmonds, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…However, it is unlikely that cetaceans respond linearly and uniformly between and among species (e.g. differential species and age-class vulnerability to each pressure, such as mother and calf known to be particularly vulnerable to speed) to an increase in the pressure score (Stepanuk et al, 2021). Research and empirical data are therefore needed to refine the maps by better characterising species responses to single maritime traffic pressures and to cumulative pressures.…”
Section: Discussionmentioning
confidence: 99%
“…Morphometric measurements of humpback whales were collected in the New York Bight using a DJI Phantom Pro+ (V1.0) UAV. UAV flights and detailed methods for obtaining morphometric measurements in cm are described in Stepanuk et al (2021). We obtained measurements of total body length (TL) and body widths at 5% intervals along the body axis of the whale (Figure 1a) using the open‐source platform MorphoMetriX (Torres & Bierlich, 2020) and summarized the output data for all individuals into a single output file using CollatriX (Bird & Bierlich, 2020).…”
Section: Methodsmentioning
confidence: 99%
“…Detailed instructions for model-building and scripts for scaling and estimating volume are archived on GitHub at https://github.com/natha n-hirtl e/humpb ack_3dm.git. measurements in cm are described in Stepanuk et al (2021). We obtained measurements of total body length (TL) and body widths at 5% intervals along the body axis of the whale (Figure 1a) using the open-source platform MorphoMetriX (Torres & Bierlich, 2020) and summarized the output data for all individuals into a single output file using CollatriX (Bird & Bierlich, 2020).…”
Section: Materials S and Me Thodsmentioning
confidence: 99%